The impact of working capital management on firms performance in the manufacturing sectors of Pakistan - Tahir, Mohammad (2016)
The working capital management has an important role for a firm’s success or failure because of its effect on firm’s performance and liquidity. This study is based on secondary data collected from 294 manufacturing firms listed on Karachi Stock Exchange Market for the period 2001-2012, to investigate the relationship between working capital management components and performance of the firms by using panel data analysis and generalized method of moments (GMM). The study applied analysis of variance (ANOVA) test in order to explore any differences across sectors in Pakistan. The study used four firms’ performance measures as dependent variables which include return on assets (ROA), net profitability margin (NPM), firms growth (FG) and Tobin Q. The working capital measures include cash conversion cycle (CCC), net trade cycle (NTC), current ratio (CR) and current assets to total assets ratio (CATAR). The study also used control variables such as size of the firm (LOS), firms age (FAGE), financial debt ratio (FDR), inflation (INF) and gross domestic product (GDP). The results revealed that CCC, CATAR, LOS, FAGE, FDR, INF and GDP are positive significant determinants of firm’s performance in Pakistan. In contrast, NTC is negative significant determinant of firm’s performance. Moreover, the results of ANOVA depicted that there is a significant difference among three working capital measures (CCC, NTC and CATAR) and firm’s performance on sectoral basis. In conclusion, the study proved that working capital measures have significant role on firm’s performance and there is a significant difference among their effects on sectoral basis, as an efficient working capital management leads to success in the performance of manufacturing sectors of Pakistan.